On the role of Zn doping on tuning the electronic and optical properties of MnCr2O4 spinel via Mn0.5Zn0.5Cr2O4 doping scheme: A first-principles quantum computational analysis. (1st April 2022) - Nadeem, Asif; Bashir, Azmat Iqbal; Azam, Sikander; Rahman, Amin Ur; Iqbal, Muhammad Azhar
Abstract: Herein, we report on the impact of Zn doping on electronic and optical properties of manganese di-chromium oxide spinel MnCr2 O4 via Mn0.5 Zn0.5 Cr2 O4 doping scheme. For the quantum computational analysis on the targeted properties, we employed first-principles density functional theory approach within full-potential linearized augmented plane wave method by Modified Becke–Johnson potential. The calculated partial and total density of states revealed a strong hybridization among electronic orbitals of the constituent species while the asymmetric spin-polarized profiles of density of states showed magnetic nature of the spinels. The major interspecies spin interaction in the degenerate valence band is via (Mn ↑ + Cr ↑ + O ↑ ) from −7 eV to Fermi level for spin up polarization. Interestingly, we predict a reduction in band gap of MnCr2 O4 to order 1eV subjected to the Zn doping, which considerably modified the electronic and optical properties of the doped spinels Mn0.5 Zn0.5 Cr2 O4 in contrast to its undoped counterpart. In particular, we predict an enhancement in absorption coefficient, energy loss function, reflectivity, dielectric constant and refractive index for Mn0.5 Zn0.5 Cr2 O4 spinels at some regions of ultraviolet energy spectrum. The calculated static refractive index of MnCr2 O4 is 1.59 and for Mn0.5 Zn0.5 Cr2 O4 it is 1.4. The optoelectronic properties indicate the promising prospects of the Zn-doped spinels for potential application in optoelectronic devices.